1978
DOI: 10.1080/03015521.1978.10426039
|View full text |Cite
|
Sign up to set email alerts
|

A classification of pasture and fodder plants according to their ability to translocate sodium from their roots into aerial parts

Abstract: The ability of the more important pasture and fodder plants grown in New Zealand to translocate sodium from their root systems into their leaf tissue was examined in a glasshouse pot experiment. Plants were classified into two distinct types: natrophilic plants, which have the capacity to accumulate large amounts of sodium in their shoots where adequate quilntities of sodium are present in the growth medium, but have low concentrations in their roots~ and natrophobic plants for which the converse is generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Displacement of K by Na in plant tissue, as opposed to substitution, is a common characteristic of natrophiles such as perennial ryegrass, and tends to be most pronounced when K supply is limited (Smith et al, 1978) and/or when external Na levels are high (Jarvis, 1982). It has been suggested that this displacement of K by an ion (Na +) of weaker ionic charge may reduce the competition for adsorption sites and favour plant uptake of divalent cations such as Ca and Mg (Chiy and Phillips, 1993a).…”
Section: Discussionmentioning
confidence: 99%
“…Displacement of K by Na in plant tissue, as opposed to substitution, is a common characteristic of natrophiles such as perennial ryegrass, and tends to be most pronounced when K supply is limited (Smith et al, 1978) and/or when external Na levels are high (Jarvis, 1982). It has been suggested that this displacement of K by an ion (Na +) of weaker ionic charge may reduce the competition for adsorption sites and favour plant uptake of divalent cations such as Ca and Mg (Chiy and Phillips, 1993a).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the above results emphasise the urgent need to consider fertiliser use more closely in terms of both plant and animal requirements; plant analysis and a balance sheet approach, as outlined, for example, by Middleton & Smith (1978), seem the most appropriate means of doing this.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, the use of sodium fertilisers to increase the sodium content in plants to an acceptable level for animal nutrition appears to be limited, especially since their effectiveness depends largely on the potassium status of the pastures, the rate at which sodium is lost from the root zone by leaching under the humid conditions which prevail in this country, the plant species (Smith et al 1978), and on the sodium salt used in the fertiliser (Lehr 1960). Because of these limitations, the most effective method for correcting sodium deficiencies in grazing animals is direct supplementation, either by salt licks or by the addition of.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, shoot and root Cl − concentrations were significantly higher for plants irrigated with the Cl − water type, and shoot and root total S concentrations were significantly higher for the plants irrigated with SO 4 2− water type (Fig. Alfalfa is included in the group of the natrophobic species (Smith et al, 1978), which can concentrate Na + in their roots, thereby decreasing the translocation to shoots. Also, the concentrations of other ions (Na + , Ca 2+ , Mg 2+ , and K + ) were different between water composition types at the same EC.…”
Section: Ion Concentrationsmentioning
confidence: 99%